Evaluating the quality and safety of the BreastScreen remote radiology assessment model of service delivery in Australia. (April 2023) - Lindsay, Daniel; Bates, Nicole; Callander, Emily; Johnston, Karen; Carlisle, Karen; Smith, Deb; Evans, Rebecca; Larkins, Sarah
Introduction: Breast cancer is the most commonly diagnosed cancer in Australian women. Given the diverse geography and populations within Australia, the ability to offer a telemedicine-supported breast screening and assessment service may increase access. The aim of this study was to assess clinical outcomes of a telemedicine-based remote radiology assessment service delivery model for detecting breast cancer in regional Australian women compared to the traditional radiologist onsite model. Methods: This study was a pre–post intervention study using de-identified administrative data. Data were collected from seven sites across three health jurisdictions within Australia. There were a total of 21, 117 assessment visits, with 10, 508 (49.8%) pre- and 10, 609 (50.2%) post-remote model implementation. Of the 10, 609 post-remote model visits, 3, 904 (36.8%) were under the remote model. The main outcome was cancer detection, split into any cancer, any invasive cancer or any small invasive cancer. Timeliness of assessment was also examined. Results: After adjusting for multiple factors, there were no statistically significant differences in cancer detection rates between the remote and onsite models (adjusted odds ratio (AOR) = 1.02, 95% CI 0.86–1.19, n.s.). Implementing the remote assessment model had statistically significant positive effects on the timeliness of assessment (AOR = 0.68, 95% CI 0.59–0.77, p < 0.001). Discussion: This study found the remote model delivers safe and high-quality assessment services, with equivalent rates of cancer detection and improved timeliness of assessment when compared to the traditional onsite model. Careful monitoring and ongoing evaluation of any health-service model is important for ongoing safety, efficiency and acceptability.